Atrial fibrillation in elite athletes. What is missing? - Tsougos, E; Giallafos, E; Paraskevaidis, I (Journal of Cardiology and Cardiovascular Medicine, 2022)
Although the beneficial effect of physical activity in the general population is well established, in elite athletes under vigorous physical activity, the effect on the electrical system of the heart is controversial. Indeed, several studies have shown an increased rate of atrial fibrillation among athletes, whereas others suggest that improved exercise capacity with training reduces atrial fibrillation recurrence. The pathophysiologic explanation of that discrepancy is missing, although several underlying mechanisms have been proposed. Taking into account the current knowledge, it seems that, although the beneficial effects of exercise are well recognized, there are conflicting data regarding the relation of the occurrence - the rate of atrial fibrillation to high-volume exercise and too long-term training. Its significance on the quality of life especially in highly trained athletes remains to be elucidated. Therefore, this short review will try to discuss this discrepancy and hopefully underlie the arising arguments.